2002
DOI: 10.1101/lm.52202
|View full text |Cite
|
Sign up to set email alerts
|

The Contextual Modulation of Conditioned Taste Aversions by the Physical Environment and Time of Day Is Similar

Abstract: In a pair of experiments, we have compared the ability of changes of place (Exp. 1) and changes of time of day (Exp. 2) to separately modulate learned saline-aversion memory phenomena in rats. Neither a spatial nor a temporal change disrupted latent inhibition using the present behavioral procedure. However, pre-exposure to the taste increased the contextual control of the learned aversion expression. The aversion reappeared in the place or at the time of conditioning after extinction in a different context. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
(30 reference statements)
2
25
1
Order By: Relevance
“…In this experiment, we used 4 days of habituation to the temporal context. Temporal specificity of latent inhibition of CTA under long periods of contextual habituation has been described (Molero-Chamizo, 2013), but a short period seems to be a factor that hinders the contextual effect on taste aversion (Morón et al, 2002). The results of this study complement our knowledge of this phenomenon because they show that an exposure without restriction to the taste stimulus under a long period of contextual habituation facilitates the temporal specificity of the latent inhibition of CTA.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In this experiment, we used 4 days of habituation to the temporal context. Temporal specificity of latent inhibition of CTA under long periods of contextual habituation has been described (Molero-Chamizo, 2013), but a short period seems to be a factor that hinders the contextual effect on taste aversion (Morón et al, 2002). The results of this study complement our knowledge of this phenomenon because they show that an exposure without restriction to the taste stimulus under a long period of contextual habituation facilitates the temporal specificity of the latent inhibition of CTA.…”
Section: Discussionsupporting
confidence: 75%
“…The magnitude of a conditioned taste aversion (CTA) can be modulated by a change in the time of day between conditioning and test (Manrique, Gámiz, Morón, Ballesteros, & Gallo, 2009;Morón et al, 2002). This procedure shows that animals tested in temporal contexts different from that of the conditioning acquire less aversion, which is similar to what has been consistently described by changing the spatial context (Boakes, Elliot, Swinbourne, & Westbrook, 1997;Bonardi, Honey, & Hall, 1990;Bouton, 1993;Bouton, Westbrook, Corcoran, & Maren, 2006;González, Garcia-Burgos, & Hall, 2012;Pearce & Bouton, 2001;Rosas & Bouton 1997).…”
Section: Taste Stimulus Restriction Temporal Contextmentioning
confidence: 50%
See 1 more Smart Citation
“…However, the influence of temporal context in associative processes is also a good model for understanding the mechanisms of learning and memory [133]. Regarding the modulating effect of time of day, we have shown in our laboratory that the time of day in the sleep/wake cycle acts as a contextual cue and modulates latent inhibition of taste aversion learning [134] and CTA retrieval [135].…”
Section: Effects Of Context On Taste Learningmentioning
confidence: 98%
“…Temporal context dependency also seems to be mediated by the hippocampus in the paradigm of latent inhibition of taste aversion learning [147], as well as in CTA [14]. However, no studies have reported the role of the amygdala in the temporal modulation of taste learning [134,135]. It is possible that the amygdala is involved in CTA selectively but not in the phenomenon of latent inhibition in this paradigm, nor in the contextual dependency of this phenomenon.…”
Section: The Limbic System and The Effect Of Context On Ctamentioning
confidence: 99%